Hypocalcaemia Secondary to Iatrogenic Hypoparathyroidism as a Rare Cause of Dilated Cardiomyopathy - Ahmed Omer, Sawsan; Elhadi, NazikElmalika Hayder (Gezira Journal of Health Sciences, 2015)
Postoperative hypocalcaemia caused by hypoparathyroidism is one of the most common morbidities of total thyroidectomy. Hypoparathyroidism is associated with chronic hypocalcaemia which can have a variety of manifestations including cardiovascular changes. Hypocalcaemia is a very rare reversible cause of dilated cardiomyopathy (DCM) which can concern one or both ventricles.  In this article, we present a case of iatrogenic hypoparathyroidism leading to hypocalcaemia, associated with systolic dysfunction of left ventricle presenting as congestive cardiac failure due to dilated cardiomyopathy in addition to other manifestations of hypocalcaemia. After treatment of heart failure and calcium-vitamin D supplementation, signs and symptoms of heart failure improved rapidly.